Field evapotranspiration and water consumption of dryland spring corn - Zhang, Jıng; Daı, Yılun (Bangladesh Journal of Botany, 2025)
Soil reservoirs are the foundation for stable grain production and sustainable development in dryland agricultural areas. This study combines long-term field positioning experiments to study the changes in soil moisture of spring maize in the Changwu Arid Plateau in the southern Loess Plateau from 2021 to 2024, and analyzes the interannual and intra annual variation characteristics and dynamic laws of soil reservoirs. The results showed that there was a significant deficit in soil reservoirs during dry years, with a deficit of 94.3 mm in the second season and 123.7 mm in the fourth season, and negative compensation in water balance was observed. In the year of abundant water, the soil reservoir had a significant surplus (208.6 mm), and the water balance showed positive compensation. The water source for evapotranspiration and water consumption during the growth period of spring corn indicated that, in wet years, it came solely from precipitation during the growth period, whereas in dry years, it was derived partly from precipitation and partly from soil water storage from the previous season. The water status of soil reservoirs had a significant impact on the growth of spring maize, and the water storage function of soil reservoirs was of great importance in alleviating the adverse effects of drought on crop growth. Bangladesh J. Bot. 54(3): 823-829, 2025 (September) Special